3D colour marker based tracking of surgical tool in image-guided surgery - Sediono, Wahju; Saaidon, Nur’Ain (Institute of Electrical and Electronics Engineers Inc., 2017)
Image-Guided Surgery (IGS) uses computer tech-nology with graphical display for pre-surgical planning and for guiding or performing surgical intervention. Medical navigation system in IGS can provide two functionalities; visualization and guidance of the surgical tool’s motion. Tool tracking in visualization is very important for accuracy and precision. In this work an optical tracking using colour markers is being proposed as an alternative method for the tool detection and tracking process in the medical navigation system. The proposed system is developed using C++ for real time accuracy. Graphical user interface is also included for system control and online monitor-ing display. Our lab experiments show that the proposed navigation system can track the surgical tool which is attached with colour markers and display the 3D position of the tool in real time. The results has shown that the proposed navigation system automatically detect any changes of the target position while the tool is moving.